The BTNL2 G16071A gene polymorphism increases granulomatous disease susceptibility: A meta-analysis including FPRP test of 8710 participants. Issue 30 (July 2016) - Tong, Xiang; Ma, Yao; Niu, Xundong; Yan, Zhipeng; Liu, Sitong; Peng, Bo; Peng, Shifeng; Fan, Hong
Abstract: Objective: The butyrophilin-like 2 ( BTNL2 ) G16071A gene polymorphism has been implicated in the susceptibility to granulomatous diseases, but the results were inconclusive. The objective of the current study was to precisely explore the relationship between BTNL2 G16071A gene polymorphism and granulomatous disease susceptibility by the meta-analysis including false-positive report probability (FPRP) test. Methods: A systematic literature search in the PubMed, Embase, and Wanfang databases, China National Knowledge Internet, and commercial Internet search engines was conducted to identify studies published up to April 1, 2016. The odds ratio (OR) with 95% confidence interval (CI) was used to assess the effect size. Statistical analysis was conducted using the STATA 12.0 software and FPRP test sheet. Results: In total, all 4324 cases and 4386 controls from 14 eligible studies were included in the current meta-analysis. By the overall meta-analysis, we found a significant association between BTNL2 G16071A gene polymorphism and granulomatous disease susceptibility (A vs G: OR = 1.25, 95% CI = 1.07–1.45, P = 0.005). The meta-regression analyses showed that a large proportion of the between-study heterogeneity was significantly attributed to the ethnicity (A vs G, P = 0.013) and the types of granulomatous diseases (A vs G, P = 0.002). By the subgroup meta-analysis, the BTNL2 G16071A gene polymorphism was associated with granulomatous disease susceptibility in Caucasians (A vs G: OR = 1.37, 95% CI = 1.18–1.58, P < 0.001). Moreover, a significant relationship between the BTNL2 G16071A gene polymorphism and sarcoidosis susceptibility (A vs G: OR = 1.52, 95% CI = 1.39–1.66, P < 0.001) was found. However, to avoid the "false-positive report, " we further investigated the significant associations observed in the present meta-analysis by the FPRP test. Interestingly, the results of FPRP test indicated that the BTNL2 G16071A gene polymorphism was truly associated with sarcoidosis susceptibility (A vs G, FPRP < 0.001). Additionally, the FPRP test confirmed that the BTNL2 G16071A gene polymorphism was associated only with granulomatous disease susceptibility among Caucasians (A vs G, FPRP < 0.001) at the level of a prior probability, which was 0.001. Conclusion: The meta-analysis indicated that BTNL2 G16071A gene polymorphism may as a likelihood factor contributed to granulomatous disease susceptibility, especially increasing the sarcoidosis susceptibility. In addition, the polymorphism may be greatly associated with likelihood of granulomatous diseases among Caucasians.